Pengaruh Penambahan Minyak Jintan Hitam (Nigella sativa) dengan Konsentrasi Berbeda pada Proses Pembuatan Yoghurt terhadap Jumlah Bakteri Asam Laktat, pH, dan Akseptabilitas - Saleh, Muhammad Rhafly; Putranto, Wendry Setiyadi; Gumilar, Jajang (Jurnal Teknologi Hasil Peternakan, 2023)
Yoghurt is a dairy product containing probiotics which have benefits for the body and can be innovated by adding flavours with the aim of attracting the interest of the people who consume it. Black cumin is one of the spices that can be used in making yoghurt. Black cumin is a spice that contains essential compounds and secondary metabolites that can improve health and contains carbohydrates that can function as prebiotics. This study aims to reveal the number of lactic acid bacteria, pH and acceptability of yoghurt added with black cumin oil. This research was conducted experimentally using a completely randomized design (CRD) with 5 concentration treatments (P0 = 0%, P1 = 0.1%, P2 = 0.2%, P3 = 0.3% and P4 = 0.4%) and 4 times repetition. Data on the number of lactic acid bacteria and pH were analysed using the test of variance and Duncan's test while the acceptability data were tested using Kruskal-Wallis and continued with the Mann-Whitney test. The results showed that the addition of black cumin oil in the manufacture of yoghurt showed a significant effect on the total bacteria, pH and acceptability of taste, aroma and total acceptance. The addition of black cumin oil with a concentration of 0.1% is a concentration that is still acceptable to the panellists and is used in the manufacture of yoghurt with a total lactic acid bacterium of 5.02 x 108 CFU/mL and a pH value of 4.39.